2021
DOI: 10.1177/2150135121994084
|View full text |Cite
|
Sign up to set email alerts
|

What Factors Should Be Considered to Improve Outcome of Mechanical Mitral Valve Replacement in Children?

Abstract: Objective: To identify risk factors for pediatric mechanical mitral valve replacement (mMVR) to improve management in this challenging population. Methods: From 1993 to 2019, 93 children underwent 119 mMVR operations (median age, 8.8 years [interquartile range [IQR]: 2.1-13.3], 54.6% females) at our institution. Twenty-six (21.8%) patients underwent mMVR at ≤2 years and 93 (78.2%) patients underwent mMVR at >2 years. Median follow-up duration was 7.6 years [IQR: 3.2-12.4]. Results: Early mortality was 9.7%,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 27 publications
0
6
0
Order By: Relevance
“…The Mayo Clinic experience has shown a temporal decrease in early mortality with time in patients <2 years (14% [1993][1994][1995][1996][1997][1998][1999][2000], 9% [2001][2002][2003][2004][2005][2006][2007][2008][2009][2010], and 0% in 2011-2019]); however, this study was limited by a relatively small sample size in this younger age group. 14 The authors attributed the improved outcomes in the last decade to early intervention, improved surgical experience, improvement in perioperative care, and implementation of updated anticoagulation protocols. The 15-mm m-MVR from St Jude Medical was approved recently by the US Food and Drug Administration and has been utilized as the smallest available m-MVR.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The Mayo Clinic experience has shown a temporal decrease in early mortality with time in patients <2 years (14% [1993][1994][1995][1996][1997][1998][1999][2000], 9% [2001][2002][2003][2004][2005][2006][2007][2008][2009][2010], and 0% in 2011-2019]); however, this study was limited by a relatively small sample size in this younger age group. 14 The authors attributed the improved outcomes in the last decade to early intervention, improved surgical experience, improvement in perioperative care, and implementation of updated anticoagulation protocols. The 15-mm m-MVR from St Jude Medical was approved recently by the US Food and Drug Administration and has been utilized as the smallest available m-MVR.…”
Section: Discussionmentioning
confidence: 99%
“…Historically, younger age at time of surgery was a major risk factor for in-hospital morbidity and mortality in comparison to older children and adolescents; early mortality in children <2 years was reported between 11% and 42% in small observational studies. 2,9,14,15 A recent large multicenter study by Ibezim and associates found that early mortality in patients <2 years was as high as 25% (36/144 patients). 8 In-hospital mortality in our investigation in neonates and infants was 11% (11/96 patients) demonstrating improved early mortality in the most recent era.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…As has been true from the outset, CHSS and ECHSA membership and leadership (past and present) make up a sizeable portion of the WJPCHS' Editorial Board. CHSS and ECHSA presidential addresses have been published in WJPCHS, 4,5 as have numerous papers presented at annual meetings [6][7][8][9] and cohort analyses from the Data Centers of both Societies. [10][11][12][13][14][15][16] Both the past and present Editors-in-Chief are past presidents of the CHSS.…”
mentioning
confidence: 99%